SOSIALISASI LITERASI DIGITAL QUR’ANI MELALUI PROGRAM ISTIQOMAH BERBASIS APLIKASI MOBILE DENGAN PENDEKATAN PARTICIPATORY LEARNING AND ACTION - Alazhari, Muhamad Roihan; Handoko, Bobi; Angella, Shelly; Yasriady, Dedy (Awal Bros Journal of Community Development, 2025)
In today's digital era, the habit of reading the Qur'an has significantly declined, especially among the younger generation. This is due to the dominance of digital activities such as social media, gaming, and other online entertainment. In response to this phenomenon, a community service team in collaboration with the Generasi Umat Terbaik Foundation (YGUT) conducted a Qur’anic literacy socialization program through the "Istiqomah" initiative, which is based on a mobile application. This activity was designed using the Participatory Learning and Action (PLA) approach, emphasizing active community involvement in the planning, implementation, and evaluation processes. The socialization was carried out through application usage training, focused group discussions, and community strengthening via the application's interactive features. The results showed an increase in participants' awareness and interest in reviving the habit of consistent Qur’anic reading, as well as the formation of a digital Qur’anic reading community network.